2014
DOI: 10.4081/hpr.2014.1389
|View full text |Cite
|
Sign up to set email alerts
|

Improving maintenance medication adherence in adult inflammatory bowel disease patients: a pilot study

Abstract: Medication nonadherence in inflammatory bowel disease (IBD) may lead to suboptimal control of the disease, decreased quality of life, and poor outcomes. This pilot study evaluated the feasibility, intervention mechanism, and potential effectiveness of a three-month continuous self-improvement (CSI) intervention to enhance medication adherence (MA) in adult nonadherent IBD patients. Adult IBD patients taking a daily or twice-daily dosed maintenance medication were screened electronically for two months to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Table 1 describes the main characteristics of the studies. Study population size ranged from 6 [ 26 ] to 784 [ 14 ] participants (mean = 128, median = 80). Most (n = 41, 87%) were in adults with only 6 studies in children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 describes the main characteristics of the studies. Study population size ranged from 6 [ 26 ] to 784 [ 14 ] participants (mean = 128, median = 80). Most (n = 41, 87%) were in adults with only 6 studies in children.…”
Section: Resultsmentioning
confidence: 99%
“…The most common EAM device type was an electronic cap fitted onto an oral medication bottle (the ‘Medication Event Monitoring System (MEMS)‘ (n = 14, 30%) [ 26 , 37 , 39 , 40 , 42 , 43 , 47 , 48 , 50 55 ] or similar (n = 10, 21%) [ 38 , 41 , 46 , 49 , 56 61 ]. The four (9%) other studies of oral medicines used electronic medication blister cards [ 14 , 62 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies showed no significant effect on medication adherence, 36,46,52,53,55,56,63,65 but two of these were pilot studies only. 52,55 These varied across length of intervention from 15 minutes 63 to 12 months 36,46,[64][65][66] and follow-up from 1 month 63 to 14 months.…”
Section: Ineffective Interventionsmentioning
confidence: 98%
“…[71][72][73][74][75][76] Objective physiological measures (blood and urine tests), calendars and diaries were less commonly used, and almost half the studies used a combination of methods to measure adherence. 4,51,[54][55][56][57][58][59][60][61]64,68…”
Section: Adherence Measurementmentioning
confidence: 99%